Systematic review and qualitative evidence synthesis of patient-reported outcome measures for abdominal aortic aneurysm. Issue 4 (9th December 2016) - Duncan, R; Essat, M; Jones, G; Booth, A; Buckley Woods, H; Poku, E; Kaltenthaler, E; Keetharuth, A D; Palfreyman, S; Michaels, J
Abstract: Background: The aim was to identify and evaluate existing patient-reported outcome measures (PROMs) for use in patients with an abdominal aortic aneurysm (AAA) to inform the selection for use in surgical practice. Methods: Two reviews were conducted: a systematic review to identify valid, reliable and acceptable PROMs for patients with an AAA, and a qualitative evidence synthesis to assess the relevance to patients of the identified PROM items. PROM studies were evaluated for their psychometric properties using established assessment criteria, and for their methodological quality using the COSMIN checklist. Qualitative studies were synthesized using framework analysis, and concepts identified were then triangulated using a protocol with the item concepts of the identified PROMs. Results: Four PROMs from three studies were identified in the first review: Short Form 36, Australian Vascular Quality of Life Index, Aneurysm Dependent Quality of Life (AneurysmDQoL) and Aneurysm Symptoms Rating Questionnaire (AneurysmSRQ). None of the identified PROMs had undergone a rigorous psychometric evaluation within the AAA population. Four studies were included in the qualitative synthesis, from which 28 concepts important to patients with an AAA were identified. The AneurysmDQoL and AneurysmSRQ together provided the most comprehensive assessment of these concepts. Fear of rupture, control, ability to forget about the condition and size of aneurysm were all concepts identified in the qualitative studies but not covered by items in the identified PROMs. Conclusion: Further research is needed to develop PROMs for AAA that are reliable, valid and acceptable to patients. Abstract : Ready for use